The more you know, the less you like: A comparative study of how news and political conversation shape political knowledge and affective polarization. Issue 1 (March 2022) - Suk, Jiyoun; Coppini, David; Muñiz, Carlos; Rojas, Hernando
The contemporary communication ecology contributes to affective polarization by presenting us with extreme exemplars of disliked groups. News exposure that is associated with political discussion networks is related to greater political knowledge, yet unlike previous eras where political knowledge and tolerance went hand in hand, this is no longer the case. We employ a comparative design to examine this idea among two democracies with differing levels of journalistic professionalism and political system: Mexico and the United States. Results show that greater political knowledge is associated with affective polarization, especially for the United States. Furthermore, there was a significant indirect path between media use and affective polarization, mediated through homogeneous political talk and political knowledge, but not in Mexico.